2004
DOI: 10.1002/ajim.10341
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos‐related pleural diseases: Dimensional criteria are not appropriate to differentiate diffuse pleural thickening from pleural plaques

Abstract: Obliteration of costophrenic angle is a much more reliable sign than dimensional criteria to characterize DPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
2
6
0
3
Order By: Relevance
“…The criteria used to define pleural plaques and visceral pleural thickening in the literature are often heterogeneous and inaccurate, potentially leading to confusion 25. However, our large study has confirmed the relationships between diffuse pleural fibrosis and the existence of a functional restrictive impairment reported previously on data based on chest x-rays 4–7.…”
Section: Discussionsupporting
confidence: 83%
“…The criteria used to define pleural plaques and visceral pleural thickening in the literature are often heterogeneous and inaccurate, potentially leading to confusion 25. However, our large study has confirmed the relationships between diffuse pleural fibrosis and the existence of a functional restrictive impairment reported previously on data based on chest x-rays 4–7.…”
Section: Discussionsupporting
confidence: 83%
“…Although studies of cohorts with occupational asbestos exposure have shown that LPT can result in restrictive spirometry,2 we were unable to identify other studies where this association was found among persons with residential exposure only. However, the Libby cohort has strong associations between restrictive spirometry and parenchymal abnormalities and DPT similar in magnitude to those found in studies of occupational cohorts 1 2 17–21…”
Section: Discussionsupporting
confidence: 65%
“…Pleural fibrosis is the most common outcome associated with inhalation of asbestos 1. Nevertheless, greater attention is typically devoted to other asbestos-related diseases associated with respiratory impairment and disability: lung cancer, mesothelioma and asbestosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ameille and his team [29] tested two differing radiological definitions of diffuse pleural thickening (pleural thickening associated with obliteration of the costophrenic angle versus pleural thickening at least 5 mm wide, extending for more than one quarter of the chest wall) for its reliability in 287 patients with asbestos-induced pleural thickening (all of them underwent HRCT). Overall, obliteration of costophrenical angle showed better reader concordance than the dimensional definition.…”
Section: Asbestosismentioning
confidence: 99%